(untitled) (Revista Brasileira de Ciências do Envelhecimento Humano, 2022)
Ageing-in-place is an umbrella term covering all aspects of living independently at home. It also emphasizes the desire of older people to stay in their well-known neighborhood with services they are familiar with and to stay in the community they know with neighbors, family, friends, and acquaintances from a long time ago. When ageing though, older people will need help and support to age-in-place, depending on the phase of ageing and the (potential) need for help or support. For ageing-in-place I have been using two constructions to distinguish the extent of support or tools that can be used to stay at home. One construction comprises the adagio My Home, Is My Castle, expressing the independent position of the older adult living at home. The other construction is Living Comfortably at Home, expressing the wish to stay as long as possible at home, even when having one or more chronic disorders or experiencing a functional or mental decline, with the support of family and or professional care or assistive tools. The domains in which these constructions occur will be discussed, focussing on the latter construction while also providing an insight into the potential of technological innovations to avoid the feeling of loneliness or social isolation.